Aquarium pump drive by solar cell using maximum power point tracking (MPPT) - Mohd Jozaimi Izwan, Jalaluddin (2015)
This thesis proposes the implementation of solar panel as an alternative that could generates electricity from sunlight exposure. The renewable energy that produced by solar could be used in supplying electricity to electrical equipment as well as becoming an alternative source apart from the available energy supplied by the utility. The main objective of this project is to supply the electrical energy to aquarium pump. Besides that, the maximum power point tracking (MPPT) is used to increase the power conversion efficiency of solar panel. Fuzzy logic controller is one of the MPPT method is used in this project and sun tracking system was added in this project to increase the power absorption by the solar panel. This sun tracking system embedded with light dependent resistor (LDR) which acts as a light sensor while the microcontroller is used for receiving and analysing input signal from LDR and sending the output signal to the DC motor. DC motor will be the medium for moving the solar panel towards the direction of the sun. The purpose of moving the solar panel towards the direction of the sun is to increase the rate of sunlight absorption by the solar panel hence increasing the electrical energy produced by solar panel. The method of fuzzy logic controller implemented using Arduino Uno to control MOSFET that contained in the dc-dc boost converter. Control signal produced by Arduino Uno will be sent to optocouple circuit as to increase the suitable voltage value to control the MOSFET. This method also presenting real-time code of fuzzy logic in Arduino language for controlling ATmega328 that contained in Arduino Uno board. The result obtained through the coding of Arduino is the variation of duty cycle of PWM signal according to the voltage of solar panel. The final result obtained from dc-dc boost converter showed that the output voltage has been regulated. Overall, the fuzzy logic controller was increases the efficiency of the overall system by 24.4965%.